Metabolic correlates of health-related quality of life among overweight and obese adolescents - Chih-Ting Lee; Chung-Ying Lin; Carol Strong; Yu-Fang Lin; Yen-Yin Chou; Meng-Che Tsai (BMC, 2018)
Abstract Background Little is known about the metabolic factors associated with the health-related quality of life (HRQOL) among obese youths. The aim of this study is to assess metabolic correlates of HRQOL in a clinical sample of Taiwanese overweight and obese (OW/OB) adolescents. Methods OW/OB adolescents (age 11-19 years) were recruited and compared to their normal-weight counterparts in a tertiary hospital. HRQOL was assessed by the Pediatric Quality of Life Inventory (PedsQL). Student t tests and Cohen's d were used to compare the differences in the PedsQL scores between normal-weight and OW/OB participants who were stratified by their cumulative number of cardiometabolic risk factors (CRF). Pearson's correlation and multivariate linear regression analyses were applied to identify predictors of PedsQL. Results OW/OB adolescents (n = 60) reported lower PedsQL scores than those of normal-weight peers. The negative effects were even larger in OW/OB participants with more than one CRF. Body mass index z-scores and serum alanine aminotransferase (ALT) levels were negatively correlated with overall and subscales of PedsQL (r = − 0.283 to − 0.431). Multivariate linear models showed ALT to be the most salient factor associated with poor obesity-related HRQOL. Conclusion Taiwanese OW/OB adolescents, particularly those having additional CRF, reported worse HRQOL. Impaired liver functions may predispose OW/OB subjects to even worse HRQOL.